Divisions of labor in the thiamin biosynthetic pathway among organs of maize - Guan, Jiahn-Chou; Hasnain, Ghulam; Garrett, Timothy J.; Chase, Christine D.; Gregory, Jesse; Hanson, Andrew D.; McCarty, Donald R. (Frontiers in Plant Science, 2014)
The B vitamin thiamin is essential for central metabolism in all cellular organisms including plants. While plants synthesize thiamin de novo, organs vary widely in their capacities for thiamin synthesis. We use a transcriptomics approach to appraise the distribution of de novo synthesis and thiamin salvage pathways among organs of maize. We identify at least six developmental contexts in which metabolically active, non-photosynthetic organs exhibit low expression of one or both branches of the de novo thiamin biosynthetic pathway indicating a dependence on inter-cellular transport of thiamin and/or thiamin precursors. Neither the thiazole (THI4) nor pyrimidine (THIC) branches of the pathway are expressed in developing pollen implying a dependence on import of thiamin from surrounding floral and inflorescence organs. Consistent with that hypothesis, organs of the male inflorescence and flowers are shown to have high relative expression of the thiamin biosynthetic pathway and comparatively high thiamin contents. By contrast, divergent patterns of THIC and THI4 expression occur in the shoot apical meristem, embyro sac, embryo, endosperm, and root-tips suggesting that these sink organs acquire significant amounts of thiamin via salvage pathways. In the root and shoot meristems, expression of THIC in the absence of THI4 indicates a capacity for thiamin synthesis via salvage of thiazole, whereas the opposite pattern obtains in embryo and endosperm implying that seed storage organs are poised for pyrimidine salvage. Finally, stable isotope labeling experiments set an upper limit on the rate of de novo thiamin biosynthesis in maize leaf explants. Overall, the observed patterns of thiamin biosynthetic gene expression mirror the strategies for thiamin acquisition that have evolved in bacteria.